Are coffeeshops really third places? A street segment approach to investigate the influence of coffee shops on property and violent crime - Boehme, Hunter M (Criminal justice studies, 2022)
Scholars have begun to investigate whether coffee shops offer neighborhoods a platform to develop social cohesion and prevent crime in the nearby area. However, no such study has examined this relationship at the street segment level. Thus, the current study takes a micro-level, geospatial approach to investigate whether the presence of coffee shops is associated with property and violent crimes at the street segment. Findings from multiple count regression models find that street segments with coffee shops were associated with increases in property crimes and all crimes grouped together, compared to streets with other businesses but no coffee shop. However, there were no statistically significant associations between street segments with coffee shops and violent crime. Findings run contrary to previous investigations of the coffee shop-crime relationship, indicating more research is needed in this area. Further investigation into the type of crime that may be associated with coffee shop presence is warranted. Theoretical and research implications are discussed.